(3GdChGFds - (3GdMSf Hf YHO Gddg Hf Sgd Hf SYjO GHf jMji Hf egQGf GdnYrSncQj, CHh gdGd,J (B395 (3g` s ((3CMeO Hf GdebQF GdeDOH s)
(3ChdgG (B:s
(3hbGd BNQ (B: (3YQVJ hLgi hOfG EfWdGbi hGdeGA jafi hGdKfGA HGbi hNjQ GdYde eG jfaY , hCfaYg eG jMGVQ Hg hbO QCjJ CcKQ GdNGUI hLd GdYGeI dgLjf HGdSDGd s
(3BNQgG (B:s
(3bGd CHh gdGd hgPG GdNHQ Odjd Ydi Cf GdCeQ GdPi YbOg fhad GHf YHO efGa Hjf GdYQH hGdaQS cGf bO EfJbV ai GdCU d(B: (3gPG BNQ eG NQL dfG ef GdChGFd , hEf NQL TF BNQ CdMbfGg Hg s
(3jJVef ChGFd GdCTjGA ef GdC(B'(3eGd hGdCaYGd hGdCbhGd ai GdLGgdjI hGdESdGe cJHJ Hbde eVHhWs
(3fbdgG GdfGSN ef fSNI cJHJ SfI (B620(3g` HChdgG JedcGJ heWGdYGJ efgG eWGdYI eDQNI SfI (B1049(3g`s
(3HBNQgG HYV JbWjY hJQbjY ai GdeYgO fSNI CNQi HQbe (B921(3JGQjNs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs